(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2016)
Publisher Adelphi has recently published in the collection “La Nave di Argo” all the works by Leonardo Sciascia, edited by Paolo Squillacioti. This paper examines how Squillacioti edited the texts: he corrected misprints and textual errors in order to provide to the readers a text as correct as possible, without being “invasive”: in fact, the editor decided to explain his work in the Editor Note, placed at the end of the book, where he reconstructs the genesis and the evolution of Sciascia’s works.